International intellectual property and the ASEAN way : pathways to interoperability / edited by Elizabeth Siew-Kuan Ng, Graeme W. Austin. - Ng, Elizabeth Siew-Kuan; Austin, Graeme W. (Cambridge University Press, 2017)
The Association of Southeast Asian Nations (ASEAN) is actively seeking ways for member countries to enhance their individual economic development within the context of overall regional advancement. Central to this is the creation of a regional intellectual property framework. This book examines the efforts to move beyond sovereign protections of intellectual property rights and establish meaningful inter-state cooperation on intellectual property issues. Rather than aim for IP harmonization, ASEAN recognizes its internal diversity and pursues an agenda of 'IP Interoperability'. The essays in this collection examine the unique dynamics of 'interoperability', analyzing the administration of intellectual property in a part of the world that is of increasing importance. The book enables the reader to compare and contrast the ASEAN model to other approaches in regional cooperation, such as Europe and Latin America, and also explores private international law as a potential vehicle for interoperability.